Enhanced desalination of polyamide thin film nanocomposite incorporated with acid treated multiwalled carbon nanotube-titania nanotube hybrid - Wan Azelee, Ihsan (Elsevier Science BV, 2017)
Polyamide (PA) thin film nanocomposite (TFN) membrane incorporated with multiwalled carbon nanotubes-titania nanotube (MWCNT-TNT) hybrid was successfully fabricated. The hybrid was introduced to the PA selective layer during the interfacial polymerization (IP) of trimesoyl chloride (TMC) and m-phenylenediamine (MPD) monomers over porous commercial polysulfone (PS) ultrafiltration support. The resultant TFN was characterized and applied for desalination. The results revealed that the acid treated MWCNT-TNT, which act as filler in the PA membrane, improved the surface properties of the membrane in term of surface charge, surface roughness and contact angle. Consequently, the water permeability increased significantly without compromising the salt rejection performance. The highest water permeability of 0.74 L/m2 h bar was achieved for the TFN membrane containing 0.05 wt% acid treated MWCNT-TNT, which is approximately 57.45% than that of the neat PA membrane. The NaCl and Na2SO4 rejection of this membrane was 97.97% and 98.07%, respectively that is almost similar to the neat membrane.